Sex and corruption: how sexism shapes voters' responses to scandal. (1st January 2020) - Barnes, Tiffany D.; Beaulieu, Emily; Saxton, Gregory W.
ABSTRACT: Conventional wisdom suggests that voters rarely punish politicians for involvement in sex scandals. Yet, we argue that some voters are likely to hold politicians accountable for their moral transgressions. We theorize that both hostile and benevolent sexists are more likely than nonsexists to punish women for involvement in a sex scandal – but each for different reasons. We posit that women politicians involved in sex scandals activate traditional gender norms and challenge men's dominant position in the society, thus provoking hostile sexists to punish women more severely than men. Benevolent sexists are likely to punish women who fail to comply with stereotypical expectations of being pure and moral, and the men who fail to safeguard those virtues. To test our theory, we rely on a survey experiment that manipulates politician sex and scandal type. We find strong support for our expectations, indicating that sexism continues to structure evaluations of women politicians and shapes voter reactions to political scandal.